Lo-on a focus on the perception of the residents of Alangalang, Leyte regarding the "practice" - Pedrera, Gay Anne G.; Saulog, Dianne Stephanie B. (2003)
Many people subject themselves to traditional medicine practices such as lo-on for reasons like poverty, lack of medicine, health and medical services particularly in remote areas, ignorance or hopelessness, or because they develop some kind of affinity with traditional medicine practitioners which they may not have with a Western practitioner. Whatever the reason is to cater to traditional medicine practices.